Promoting global English while forging young Northeastern Thai learners’ identity - Budsaba Kanoksilapatham (Penerbit Universiti Kebangsaan Malaysia, 2016)
Globally, English is used as a central means of communication; regionally, English has been endorsed as the working language for ASEAN (Association of Southeast Asian Nations). Therefore, the need to improve Thai citizens’ English has become imperative. However, Thai learners’ English language performance has been quite unsatisfactory. AEC (ASEAN Economic Community) integration in 2015 and globalisation have brought another concern that ‘Thainess’ is being eroded due to external influences. Therefore, an effort to maintain, revive, and revitalise ‘Thainess’ has been exerted. This study aims to enhance Thai students’ global English and maintain regional “Thainess” in the northeastern region. Procedural steps in this research were carried out, integrating regional community involvement whenever possible. First, based on the community’s prominent characteristics as expressed through the completion of a questionnaire, a set of instructional innovations for elementary English education was constructed and subsequently implemented to a Grade Level 4 class at a school in the northeastern region. Two sets of pre and post-tests were constructed and administered to estimate their knowledge of regional Thainess and English vocabulary at the beginning as opposed to towards the end of the instruction. Finally, the students performed a simulated tour guide task. Their accomplished execution of the task demonstrated their integrated knowledge of Thainess and English, contributing to a sense of pride in the region and a sense of achievement in their English proficiency. In short, with the instructional innovations necessitating community involvement, this research can address the pressing needs triggered by both globalisation and regionalisation.